2024
DOI: 10.3390/bios14020107
|View full text |Cite
|
Sign up to set email alerts
|

Using Rapid Prototyping to Develop a Cell-Based Platform with Electrical Impedance Sensor Membranes for In Vitro RPMI2650 Nasal Nanotoxicology Monitoring

Mateo Gabriel Vasconez Martinez,
Eva I. Reihs,
Helene M. Stuetz
et al.

Abstract: Due to advances in additive manufacturing and prototyping, affordable and rapid microfluidic sensor-integrated assays can be fabricated using additive manufacturing, xurography and electrode shadow masking to create versatile platform technologies aimed toward qualitative assessment of acute cytotoxic or cytolytic events using stand-alone biochip platforms in the context of environmental risk assessment. In the current study, we established a nasal mucosa biosensing platform using RPMI2650 mucosa cells inside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…SLA 3D printing was used to construct the chip components and bonded to a PET membrane using the double-sided tape cut with xurography. Overall, this research demonstrated how affordable and rapid fabrication methods can be beneficial as pre-screening tools [96].…”
Section: Applications Of Using Double-sided Tapementioning
confidence: 81%
“…SLA 3D printing was used to construct the chip components and bonded to a PET membrane using the double-sided tape cut with xurography. Overall, this research demonstrated how affordable and rapid fabrication methods can be beneficial as pre-screening tools [96].…”
Section: Applications Of Using Double-sided Tapementioning
confidence: 81%